Preparation and characterization of poly(lactic acid)/linear low density polyethylene/recycled tire waste/graphene nanocomposites - Bijarimi, M.; Abdulsalam, Yaser; Ahmad, Mohammad Norazmi; Abdullah, Erna Normaya; Alhadadi, Waleed; Desa, Mohd Saiful Zaidi (Elsevier, 2023)
Biobased polymer nanocomposites are a separate class of materials created by the inclusion of nanoparticles into polymer matrix composites. In comparison to ordinary composites, these materials have superior mechanical, electrical, thermal, and barrier characteristics, as well as exceptional microstructures, which have attracted global interest. For toughness modification, poly(lactic acid) (PLA) is commonly toughened with low-modulus polymers such as linear low-density polyethylene (LLDPE). Due to environmental concerns, recycled tire waste (RW) was included in a binary blend of PLA and LLDPE and reinforced with graphene nanoplatelets (GNP). The polymer resins, RW and GNP were melt blended in a twin-screw extruder at 60 rpm for 15 min. The blends were then characterized for chemical changes, thermal transitions and thermal degradation. Due to the presence of platelets, it was discovered that the 40/50/10/5 (PLA/LLDPE/RW/GNP) nanocomposite exhibited the maximum thermal degradation temperature. Thermal transitions were observed in all nanocomposites without any appreciable chemical changes.